IDENTIFICATION OF THE CAUSES OF DELAY IN COMPLETION OF BRIDGE CONSTRUCTION WORK IN PADANG CITY - Dian Wahyoni; Delvi Novita Sari (Ikatan Dosen Menulis, 2024)
The success of a project if the time and cost can be implemented properly according to the plan, in its implementation often encountered obstacles that were not previously known. In identifying performance problem factors in delays is part of project management and is the first step in project implementation to support the success of the project itself. This can be understood because the level of identification of project delay factors can make it easier to control the project activity process. For this reason, research is needed to determine the factors that cause delays in project completion so that the project completion time is according to plan. The purpose of this study was to determine the factors that cause work delays, rank delay factors, and determine the dominant factors that cause delays that can affect the performance of construction implementation on the Andalas University Hospital Bridge construction project in Padang City. This study is a quantitative study, with data collection techniques conducting surveys by distributing questionnaires, interviews with respondents, with data processing using SPSS ver.26. The results of the analysis are presented in the form of graphs and tables then categorized based on their indicators. The results showed that the most dominant factors causing delays in the implementation of the Andalas University Hospital Bridge construction project in Padang City were changes in implementation methods, delays in material delivery, unexpected weather conditions, and late mobilization of equipment.